1975
DOI: 10.1055/s-0028-1106210
|View full text |Cite
|
Sign up to set email alerts
|

Basale und reaktive Proinsulin- und Insulinsekretion bei Frauen mit Übergewicht

Abstract: Serum proinsulin and insulin levels were measured on 55 normal or overweight women before and after oral glucose administration. The proinsulin proportion of basal total insulin was 70% in women of normal weight. With increasing overweight the relation shifted in favour of insulin. After stimulation with glucose, proinsulin levels were significantly raised, analogous to total insulin, but les marked than the latter. The increased total insulin excretion in obesity was, therefore, largely due to insulin and les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1975
1975
1988
1988

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The enzymatic degradation method, which is quick and requires only small volumes of serum, seemed an attractive alternative to gel filtration. However, it recorded consistently higher fasting values [5,7] (e. g., 70% proinsulin in normal women [22]) than those recorded by gel filtration. Lately, it has been demonstrated that the degradation of insulin is only partial and dependent on its concentration, and that proinsulin, too, is degraded to some degree [7].…”
Section: Methodology Sources Of Errormentioning
confidence: 70%
“…The enzymatic degradation method, which is quick and requires only small volumes of serum, seemed an attractive alternative to gel filtration. However, it recorded consistently higher fasting values [5,7] (e. g., 70% proinsulin in normal women [22]) than those recorded by gel filtration. Lately, it has been demonstrated that the degradation of insulin is only partial and dependent on its concentration, and that proinsulin, too, is degraded to some degree [7].…”
Section: Methodology Sources Of Errormentioning
confidence: 70%